A toroidal SAW gyroscope with focused IDTs for sensitivity enhancement - Lu Tian; Haitao Zhao; Qiang Shen; Honglong Chang (Microsystems & Nanoengineering, 2024)
Abstract A surface acoustic wave (SAW) gyroscope measures the rate of rotational angular velocity by exploiting a phenomenon known as the SAW gyroscope effect. Such a gyroscope is a great candidate for application in harsh environments because of the simplification of the suspension vibration mechanism necessary for traditional microelectromechanical system (MEMS) gyroscopes. Here, for the first time, we propose a novel toroidal standing-wave-mode SAW gyroscope using focused interdigitated transducers (FIDTs). Unlike traditional SAW gyroscopes that use linear IDTs to generate surface acoustic waves, which cause beam deflection and result in energy dissipation, this study uses FIDTs to concentrate the SAW energy based on structural features, resulting in better focusing performance and increased SAW amplitude. The experimental results reveal that the sensitivity of the structure is 1.51 µV/(°/s), and the bias instability is 0.77°/s, which are improved by an order of magnitude compared to those of a traditional SAW gyroscope. Thus, the FIDT component can enhance the performance of the SAW gyroscope, demonstrating its superiority for angular velocity measurements. This work provides new insights into improving the sensitivity and performance of SAW gyroscopes.